Proximate, Nutrient Composition and Glycemic Index of Pearl Millet-Acha-Moringa Blend (Journal of Environmental Bioremediation and Toxicology, 2023)
Globally, grains can be regarded as the daily source of diets for many populations. They constitute cereals, pseudocereals and legume and are majorly the seeds of plants. They are made up of a wide variety of macronutrients that are vital   to human diet, those nutrients are not limited to carbohydrates, but also proteins lipids and micronutrients such as vitamins and minerals. Grains can be consumed as a source of dietery fibre and bioactives. This research is aimed at formulating a diet using whole grains and cray fish and also to determine the nutrients composition of the diet and its Glycemic Index. A diet was formulated using whole Pearl millet, whole Hungary rice, moringa leaves and cray fish. The Glycemic Index of the diet and the nutrients composition of the formulated diet such as % Fat, % Ash, % Moisture, %Fiber and Vitamin E were determined. Iron and magnesium ions concentration was determined using Atomic Absorption Spectrophotometry while calcium ion was determined using Flame Photometry.  The result showed that the blend contains 6.31% moisture, 1.24% ash, 1.50% fat, 12.06% protein, 3.22% fibre, 75.66% carbohydrate, 50.22 mg Vitamin E, 1.37 mg Magnesium (Mg), and the Glycemic Index was 67.7%.
Keywords: Formulated Diet; Moringa oleifera; Pearl millet; Hungary rice; Cray fish